Ethnic Differences in the Initiation and Duration of Breast Feeding – Results from the Born in Bradford Birth Cohort Study. Issue 4 (15th April 2013) - Santorelli, Gillian; Petherick, Emily; Waiblinger, Dagmar; Cabieses, Baltica; Fairley, Lesley
Abstract Background Initiation of breast feeding and duration of any breast feeding are known to differ by ethnic group, but there are limited data on differences in exclusive breast feeding. This study aimed to determine if there are ethnic differences in the initiation and duration of any and exclusive breast feeding. Methods Breast‐feeding data were obtained from a subsample of 1365 women recruited to a multi‐ethnic cohort study (Born in Bradford) between August 2008 and March 2009. Poisson regression was used to investigate the impact of socio‐economic, life style and birth factors on ethnic differences in the prevalence of breast feeding. Results Compared with white British mothers, initiation of breast feeding was significantly higher in all ethnic groups and this persisted after adjustment for socio‐economic, life style and birth factors [Pakistani: prevalence rate ratio (PRR) = 1.19 (95% confidence interval 1.10, 1.29); Other South Asian: PRR = 1.29 (1.18, 1.42); Other ethnicities: PRR = 1.33 (1.21, 1.46)]. There were no differences in exclusive breast feeding at 4 months [Pakistani: PRR = 0.77 (0.54, 1.09); Other South Asian: PRR = 1.55 (0.99, 2.43); Other ethnicities: PRR = 1.50 (0.88, 2.56)]. Any breast feeding at 4 months was significantly higher in mothers of all non‐white British ethnicities [Pakistani: PRR = 1.27 (1.02, 1.58); Other South Asian: PRR = 1.99 (1.52, 2.62); Other ethnicities: 2.45 (1.86, 3.21)]. Conclusions Whilst women of ethnic minority groups were significantly more likely to initiate breast feeding and continue any breast feeding for 4 months compared with white British women, the rates of exclusive breast feeding at 4 months were not significantly different once socio‐economic, life style and birth factors were accounted for.